Synthesis and Antibacterial Activity of Some New 2-Aminopyrimidines and 2-(1H) Pyrimidinones - M. Barot, Vijay (Asian Journal of Chemistry, 2010)
Several related 2-amino-4-(2'-hydroxy-4'-ethoxy phen-1' -yl)-6- substituted phenyl pyrimidine and pyrimidinone compounds are prepared with a view to the fact that a number of related compounds are known to possess biological activity.